Conclusions of the Joint WHO/UNICEF/IAEA/IZiNCG Interagency Meeting on Zinc Status Indicators - De Benoist, Bruno; Darnton-Hill, I.; Davidsson, L.; Fontaine Olivier; Hotz, Christine (SAGE Publications, 2007)
Zinc deficiency is an important cause of morbidity in developing countries, particularly among young children, yet little information is available on the global prevalence of zinc deficiency. A working group meeting was convened by the World Health Organization (WHO), the United Nations Children’s Fund (UNICEF), the International Atomic Energy Agency (IAEA), and the International Zinc Nutrition Consultative Group (IZiNCG) to review methods of assessing population zinc status and provide standard recommendations for the use of specific biochemical, dietary, and functional indicators of zinc status in populations. The recommended biochemical indicator is the prevalence of serum zinc concentration less than the age/sex/time of day-specific cutoffs; when the prevalence is greater than 20%, intervention to improve zinc status is recommended. For dietary indicators, the prevalence (or probability) of zinc intakes below the appropriate estimated average requirement (EAR) should be used, as determined from quantitative dietary intake assessments. Where the prevalence of inadequate intakes of zinc is greater than 25%, the risk of zinc deficiency is considered to be elevated. Previous studies indicate that stunted children respond to zinc supplementation with increased growth. When the prevalence of low height-for-age is 20% or more, the prevalence of zinc deficiency may also be elevated. Ideally, all three types of indicators would be used together to obtain the best estimate of the risk of zinc deficiency in a population and to identify specific subgroups with elevated risk. These recommended indicators should be applied for national assessment of zinc status and to indicate the need for zinc interventions. The prevalence of low serum zinc and inadequate zinc intakes may be used to evaluate their impact on the target population’s zinc status.